One dimensional proteome analysis of Andrographis Paniculata - Chan, Wan Jo, 1991-, author 609218 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains (Biologi - Industri)) - Universiti Teknologi Malaysia, 2016